Edukasi Latihan Fisioterapi Komunitas Dalam Mengurangi Carpal Tunnel Syndrome Pada Posyandu Anak Dan Lansia Di RW 3 Rampal Celaket - Syarif Hidayatullah; Simon Panyonga; Qonita Nabila; Dinda Permata Putri; Niswatul Chamidah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
As older people age, their muscle strength typically declines, including the weakening of the thenar muscles over time which can lead to a blockage of the median nerve often known as carpal tunnel syndrome. This blockage causes pain that can radiate from the shoulder to the fingertips. This counseling is designed to provide older adults with knowledge and training on hand pain, including its symptoms and triggering factors. The counseling method uses presentations to explain information to the elderly with the aim of health promotion. In addition, there was a question and answer session and education on exercises that can be done at home. The counseling process went smoothly, the elderly could follow and understand the exercises taught to be done at home. This counseling has the potential to reduce pain in the elderly after they do the exercises at home. Counseling activities at the Children and Elderly Posyandu Rw.3 Rampal Celaket, Klojen District, Malang City helped increase the understanding of the elderly about pain in the hands caused by median nerve blockage.